Educazione al pensiero e affettività in Matthew Lipman - Francesca Pulvirenti (Firenze University Press, 2011)
Even an essay on the philosophy for children (P4C) and the exercise of thought. An exercise that, according to the author of the essay is educational practice. The P4C is an important contribution to educational activity which aims to restore to the children 'rights of thought'. This is largely thanks to M. Lipman who has always supported the theory of multidimensional thinking of the child. The author insists on the concept of community because each group should be turned into a community to develop feelings of friendship and love. The P4C is proposed as a tool to think and feel other-minds, and the author presents us a laboratory experience.